Aak to Zumbra a dictionary of the world's watercraft (Mariners' Museum, 2000)
"Boat lovers will rejoice when they see this delightful new dictionary of indigenous watercraft from around the world. This reference work is both a great contribution to 'the ethnography of the boat' and includes boats with such names as zumbra and abubuz, making it a treasure trove of terms for Scrabble players everywhere. Accompanied by line drawings, the 5,600 entries list country of origin, function, dates of operation, and appearance."--"Outstanding Reference Sources," American Libraries, May 2002.